1997
DOI: 10.1161/01.cir.95.9.2286
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Captopril and Nitrates on Muscle Sympathetic Nerve Activity in Volunteers

Abstract: Thus, captopril suppressed MSA despite lowering of diastolic blood pressure but allowed normal adaptation of the SNS during mental or physical stress. In contrast, the nitrate strongly activated the SNS under baseline conditions. These findings demonstrate that vasodilators differentially interact with the SNS, which could be of importance in therapeutic strategies for the treatment of patients with cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 51 publications
4
24
0
1
Order By: Relevance
“…25 Hence, arterial baroreceptors may have been activated by methoxamine, although arterial pressure and filling pressure of the left heart were similar to baseline values. In agreement with Noll et al, 26 who found unchanged muscle sympathetic nerve activity in conjunction with reduced diastolic blood pressure after oral short-term administration of captopril to healthy subjects, we found unchanged muscle sympathetic nerve activity after intravenous administration of enalaprilat, suggesting resetting of the baroreflex control of muscle sympathetic nerve activity to lower blood pressures. This notion is further supported by the findings of Matsukawa et al, 27 who examined muscle sympathetic nerve activity in healthy subjects during equipotent infusions of Ang II and phenylephrine.…”
Section: Discussionsupporting
confidence: 93%
“…25 Hence, arterial baroreceptors may have been activated by methoxamine, although arterial pressure and filling pressure of the left heart were similar to baseline values. In agreement with Noll et al, 26 who found unchanged muscle sympathetic nerve activity in conjunction with reduced diastolic blood pressure after oral short-term administration of captopril to healthy subjects, we found unchanged muscle sympathetic nerve activity after intravenous administration of enalaprilat, suggesting resetting of the baroreflex control of muscle sympathetic nerve activity to lower blood pressures. This notion is further supported by the findings of Matsukawa et al, 27 who examined muscle sympathetic nerve activity in healthy subjects during equipotent infusions of Ang II and phenylephrine.…”
Section: Discussionsupporting
confidence: 93%
“…3,4,7 One study reported no increase in MSNA in hypertensive patients, 18 but the population included subjects of advanced age being treated with antihypertensive medications, which could affect baseline MSNA levels. 20 Another important observation of the present study is that acute hyperoxia-normalized sympathetic activity in hypertensive patients reaching the values observed in control subjects. This fact seems to confirm the hypothesis that tonic chemoreflex drive may be responsible, at least in part, for sympathetic overactivity in hypertension.…”
Section: Discussionsupporting
confidence: 67%
“…The fact that baseline BP was decreased and MSNA augmented is unlikely to affect the stress response, because isosorbide dinitrate, a vasodilator that induced similar changes in these parameters, has been shown not to alter sympathetic and BP responses to mental stress. 27 Ghrelin may possibly affect stress response through a central effect. Peripheral or intraperitoneal administration of ghrelin induces c-fos expression in the paraventricular nucleus of rats, 28 an area involved in a neural network mediating the autonomic, neuroendocrine, and skeletal-motor responses of fear and anxiety, 29 which may be a prime area for mediating the effects of ghrelin on the cardiovascular response to stress.…”
Section: Discussionmentioning
confidence: 99%